(untitled) (Journal of Interdisciplinary Insights, 2024)
Focusing on the four dimensions of “carbon calculation, carbon reduction, energy replenishment, and carbon sink”, corresponding suggestions are put forward for highway construction from the perspective of the whole life cycle, and technologies such as low-carbon roadbed pavement construction, low-carbon construction of bridge and tunnel engineering, green zero-carbon service area, and zero-carbon energy are used to promote and apply the results of carbon reduction from the planning and implementation. Keywords: Highways; Whole Life Cycle; Green and Low-carbon.